Necessary and sufficient moment conditions for the GARCH(r,s) and asymmetric power GARCH(r,s) models - Shiqing Ling; Michael MacAleer (Osaka University, Institute of Social and Economic Research (ISER), 2001)
Although econometricians have been using Bollerslev's (1986) GARCH (r, s) model for over a decade, the higher-order moment structure of the model remains unresolved. The sufficient condition for the existence of the higherorder moments of the GARCH (r, s) model was given by Ling (1999a). This paper shows that Ling's condition is also necessary. As an extension, the necessary and sufficient moment conditions are established for Ding, Granger and Engle's (1993) asymmetric power GARCH (r, s) model.
Keywords: 330